Physical activity and mental health in Chinese high school students: a cross-sectional study - Zhiyi Xu; Fucheng Zhang; Meihua Su; Xiangdong Wang (Scientific Reports)
Abstract Adolescent physical activity (PA) is essential for mental health. However, the declining PA levels amongst this group pose global challenges. This study examines the relationship between PA and mental health amongst 1668 Chinese high school students, focusing on gender and grade-level differences. Only 30.9% of students met the recommended 60 min of daily moderate-to-vigorous PA (MVPA), with boys showing a significantly higher compliance rate than girls (44.2% vs. 25.2%, P < 0.001). MVPA compliance was linked to better mental health, as compliant students had a lower mental health detection rate (43.6%) compared with non-compliant peers (56.4%, P < 0.001). The grade 11 students were at the highest risk of mental health issues (OR = 2.421, 95% CI: 1.893–3.096 and P < 0.001), whilst being female (OR = 0.630, 95% CI: 0.502–0.791 and P < 0.001). Meanwhile, MVPA non-compliance (OR = 0.792, 95% CI: 0.736–0.851 and P = 0.008) were additional risk factors. Poorer mental health correlated with reduced time in vigorous PA and increased time in low-intensity activities (P = 0.001). These findings highlight the low PA levels and significant mental health risks amongst adolescents, particularly girls and grade 11 students. Targeted interventions promoting PA, time management and mental health support are critical.